(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article explores the approaches to the formation of artistic-spatial and artisticfigurative design concepts for Devolanovskyi Descent in Odesa. Based on the analysis of academic tasks in the disciplines of DAS and diploma design, it is established that the artistic and figurative solution in architectural and design planning is derived from the artistic analysis of form, volume, space. This analysis is carried out in the language and means inherent in contemporary art. The object of the study is a fragment of the architectural environment in the form of the original spatial organization, volume or form, and the subject is the artistic and figurative interpretation of this fragment by means of formal composition. This is a kind of creative translation from the language of art to the language of project graphics. The peculiarity of this activity is the artistic mastery of the initial environmental situation, the identification of the figurative potential of the fragment of the architectural environment under study, the construction of a consistent system of impressions with an emphasis on the carrier of imagery: space, form, volume, mass, detail, color, etc. The second important element of artistic comprehension is the consumer of the environment and environmental activity. The peculiarity is the combination of “freeze-frames” of easel art with artistic and staging activities, a procedural dynamic composition that provides a number of environmental impressions. Thus, environmental factors are transformed into artistic ideas and vice versa; the spheres of visual interaction between a person and a fragment of the environment are established, areas with the qualities of art objects and environmental installations appear, etc. The student works are presented, which focus on a certain potential of the architectural environment of Devolanovskyi Descent in Odesa. The peculiarity of this activity is the artistic mastery of the initial environmental situation the identification of the figurative potential of the fragment of the architectural environment under study, the construction of a consistent system of impressions with an emphasis on the carrier of imagery: space, shape, volume, mass, detail, color, etc. The second important element of artistic comprehension is the consumer of the environment and environmental activity. The peculiarity is the combination of “freeze-frames” of easel art with artistic and staging activities, a procedural dynamic composition that provides a number of environmental impressions. Thus, environmental factors are transformed into artistic ideas and vice versa; the spheres of visual interaction between a reason and a fragment of the environment are established, areas with the qualities of art objects and environmental installations appear, etc. The student works are presented, which focus on a certain potential of the architectural environment of Devolanovskyi Descent in Odesa.